Design, methodology, and baseline of eastern China student health and wellbeing cohort study - Zhang, Xiyan; Zhao, Genming; Ma, Jun; Tao, Fangbiao; Pan, Chen-Wei; Zhang, Fengyun; Wang, Yan; Yang, Wenyi; Xiang, Yao; Wang, Xin; Tian, Yunfan; Yang, Jie; et al. (Frontiers in Public Health, 2023)
Purpose: To describe the study design, methodology, and cohort profile of Eastern China Student Health and Wellbeing Cohort Study. The cohort baseline includes (1) targeted disease (myopia, obesity, elevated blood pressure and mental health) and (2) exposures (individual behaviors, environment, metabolomics, gene and epigenetics). Participants: Annual physical examination, questionnaire-based survey as well as bio-sampling have been carried out in the study population. At the first stage (2019-2021) a total of 6506 students in primary schools are enrolled in the cohort study. Findings to date: Of all the cohort participants, ratio of male/female is 1.16 among a total of 6506 student participants, of which 2728 (41.9%) students are from developed regions, 3778 (58.1%) students from developing regions. The initial age of observation is 6-10 years old, and they will be observed until they graduate from high school (＞18 years of age). (1) Targeted diseases: The growth rates of myopia, obesity and high blood pressure are different by regions, for developed regions the prevalence of myopia, obesity, elevated blood pressure is 29.2%,17.4%,12.6% in the first year respectively. For developing regions the prevalence of myopia, obesity, elevated blood pressure is 22.3%, 20.7%, 17.1% in the first year respectively. Average score of CES-D is 12.9±9.8 in developing regions/11.6±9.0 in developed regions. (2)Exposures:①First aspect of Individual behaviors, The questionnaire topics include diet, physical exercise, bullying, family etc. ②Second aspect of Environment and metabolomics, the average desk illumination is 430.78(355.84-611.56) LX, and the average blackboard illumination is 365.33(286.83-516.84) LX. Metabolomics like bisphenol A in the urine is 0.734 ng/ml.③Third aspect of Gene and epigenetics. Future plans: Eastern China Student Health and Wellbeing Cohort Study is aiming to focus on the development of student targeted diseases. For children with student common disease, this study will focuse on targeted disease related indicators. For children without targeted disease, the aim of this study is to explore the longitudinal relationship between exposure factors and outcomes, excluding baseline confounding factors. Exposure factors include three aspects:(1) Individual behaviors, (2) Environment and metabolomics, (3) Gene and epigenetics. The cohort study will continue until 2035.